Analysis of consumers’ eating attitudes having animal-origin diet - Szakály, Márk; Soós, Mihály (International Journal of Engineering and Management Sciences, 2019)
The spread of civilization illnesses realized in the developed societies has also reached the less-developed ones as well. The reason behind this phenomenon is the non-proper food consumption among the first places. This study is dealing with the plant-based nutrition and its characteristics. The authors’ aim was to examine the consumers’ opinion on the plant-based diet.